2021
DOI: 10.1111/jgs.17545
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional geriatric and palliative care intervention associated with fewer hospital days

Abstract: Background: With increasing complexity of our aging inpatient population, we implemented an interprofessional geriatric and palliative care intervention on a hospitalist service. This study aimed to measure the intervention's impact on length of stay (LOS), 30-day readmission, and the daily intensity of inpatient services utilization. Methods: Using a nonrandomized controlled intervention at a 1000-bed U.S. academic quaternary medical center, we studied 13,941 individuals admitted to a general medicine hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
5
0
3
Order By: Relevance
“…Apesar da abordagem em CP ser indicada desde o diagnóstico de uma doença ameaçadora da vida, a decisão de quando indicar e implementar cuidados exclusivamente paliativos aos pacientes idosos é uma questão complexa. Mesmo que um em cada quatro idosos gravemente enfermos, internados em alas geriátricas seja encaminhado para cuidados paliativos, não existe uma concordância sobre a melhor forma de se avaliar e comunicar o prognóstico em populações geriátricas (Min et al, 2022;Chávarri-Guerra et al, 2021). Arcanjo et al (2018) ressaltam ainda que a maioria dos familiares e cuidadores é quem solicita os cuidados paliativos aos pacientes idosos.…”
Section: Autores/anounclassified
See 2 more Smart Citations
“…Apesar da abordagem em CP ser indicada desde o diagnóstico de uma doença ameaçadora da vida, a decisão de quando indicar e implementar cuidados exclusivamente paliativos aos pacientes idosos é uma questão complexa. Mesmo que um em cada quatro idosos gravemente enfermos, internados em alas geriátricas seja encaminhado para cuidados paliativos, não existe uma concordância sobre a melhor forma de se avaliar e comunicar o prognóstico em populações geriátricas (Min et al, 2022;Chávarri-Guerra et al, 2021). Arcanjo et al (2018) ressaltam ainda que a maioria dos familiares e cuidadores é quem solicita os cuidados paliativos aos pacientes idosos.…”
Section: Autores/anounclassified
“…Portanto, agir nessa perspectiva aproxima-se das formulações teóricas, em que as pessoas idosas apresentam diversas dificuldades, como o controle da dor e de outros sintomas, os quais podem ser de dimensão física, emocional, espiritual. E, nesse agir, possibilita reciprocidade, enriquecimento mútuo, com tendência à horizontalização das relações de poder entre os profissionais envolvidos, possibilitando a troca de afetos e, saberes entre as áreas de conhecimento (Min et al, 2022). Sun et al (2020) afirmam ainda que com a pandemia da COVID-19, foi necessário que os profissionais de saúde optassem por não iniciar ou continuar terapias de sustentação da vida, dada a alta proporção de pacientes idosos com anormalidades metabólicas na internação hospitalar.…”
Section: Autores/anounclassified
See 1 more Smart Citation
“…As mentioned above, if we look at financing mechanism for the care of frail older adults in the United States, there is more fragmentation inherent in financing. 2 Acute hospital care is covered through the Medicare program. However, aftercare remains problematic.…”
Section: Funding Informationmentioning
confidence: 99%
“…8 In this issue of JAGS, Min and colleagues describe the impact of a non-randomized controlled study of an interprofessional geriatric and palliative care intervention on length of stay, 30-day readmission, and inpatient services utilization at a large, academic medical center. 9 The intervention consisted of the attendance of a geriatrician, palliative care physician, and social worker in twice-weekly multidisciplinary discharge rounds, with informal recommendations for identified geriatric or palliative care issues made to the hospitalist team. The investigators found that compared to control teams, patients cared for by the intervention hospitalist group had a 0.36 days shorter length of stay with no change in readmission rates but with a modest increase in overall relative value unit utilization.…”
mentioning
confidence: 99%